[Ethiopia-Netherlands AIDS research project] - Sanders, E; de Wit, T; Fontanet, A; Goudsmit, J; Miedema, F; Coutinho, R (2001)
The 'Ethiopia-Netherlands AIDS Research Project' (ENARP), started in 1994, is a long-term collaboration between AIDS researchers in Amsterdam and the Ethiopian Health and Nutrition Research Institute in Addis Ababa. The ENARP's primary objectives include conducting studies on HIV and AIDS in Ethiopia, especially by means of some large-scale prospective cohort studies, training Ethiopian scientists in PhD programmes in epidemiology, immunology and virology and establishing a reference laboratory for HIV and AIDS in Ethiopia and neighbouring countries. External funding for ENARP amounts to 32 million Dutch guilders for two periods of four years and is being provided by the Dutch Government. ENARP is the largest third world biomedical project supported by the Dutch Government. In 2000 two Ethiopian students obtained their doctorates from the University of Amsterdam. Five new PhD students commenced their training in 1999. ENARP hopes to set up HIV-1 vaccine phase I and phase II trials in the near future.